The Effect of Kahoot! Platform on Eleventh Grade Students’ Reading Comprehension: A New Fun Media at Sport Senior High School - Fellecia, Yolanda; Ayudhia, Honesty Yonanda (Universitas Negeri Padang, 2024)
This research used quantitative research method with quasi-experimental research. Examining the potential impact of the Kahoot! Platform on students' ability to understand what they read was the primary goal of this research. Sport Senior High School eleventh graders made up the study's population. The population consist of 168 students who are classified into six classes. XI MIPA 2 was chosen using the cluster sampling method to serve as the experimental class. The eight meetings that this investigation was conducted over during school hours. For both the pre- and post-tests, the researcher used multiple-choice exams to collect data. The exam questions are drawn from hortatory exposition texts and narrative texts. A two-tailed independent sample t-test with a significance level of 0.000 (i.e., less than 0.05) was found in the results of the data analysis. To sum up, we accept (H1) and reject the null hypothesis (H0). Finally, our study demonstrated that the Kahoot! Platform improved students’ reading comprehension.